Evaluating the effectiveness of pharmacist-led interventions on medication adherence in chronic disease management - Sahu, Prerana; Patel, Ritesh (Journal of Neonatal Surgery, 2025)
Chronic kidney disease (CKD) is a public health concern due to its increasing prevalence, multiple prescribed medications, multiple emergency visits and hospital admissions that is a burden on healthcare resources. The study was conducted to assess the rate & pattern of occurrence of drug related problems (DRPs) and clinical and economic outcomes of pharmacist interventions in CKD patients. This was a randomized, controlled, prospective, open labeled study that included patients diagnosed with chronic kidney disease of any stage who are admitted to a tertiary care hospital or visiting the ambulatory dialysis centre. Test group were actively followed by intervening pharmacist to identify DRPs and necessary changes to drug therapy and/or monitoring parameters were performed. A direct cost associated with pre-determined variables like medication prescribed, lab investigation/s ordered, length of hospital stay and adverse drug effects per admitted inpatient between control and interventional groups was evaluated and compared. The control group received usual medical care provided by healthcare professionals. Clinical pharmacist interventions can significantly improve disease control measures, improve health related quality of life, and reduce costs of drug therapy. Employing clinical pharmacists in hospitals is beneficial to patients as well as can reduce healthcare costs.